COVID-19 lessons from the National Basketball Association bubble - Can persistently SARS-CoV-2-positive individuals transmit infection to others? - Salazar, J. W.; Katz, M. H. (JAMA Internal Medicine, 2021)
A fundamental question of the COVID-19 pandemic has been when it is safe to discontinue isolation precautions in patients who have recovered. The US Centers for Disease Control and Prevention (CDC) originally recommended a test-based strategy for discontinuing isolation, requiring 2 consecutive negative reverse-transcription-polymerase chain reaction (RT-PCR) tests at least 24 hours apart. However, as experience with COVID-19 accumulated, we learned that a small number of individuals continue to shed virus long after infection. Given that it appeared that the virus from these persistently positive individuals was not replication competent1 and there was minimal risk of transmission after sufficient time passed after symptom onset,2 the CDC shifted to a symptom-based strategy in July 2020, advising that isolation and precautions can be discontinued 10 days after symptom onset or a patient`s first positive RT-PCR result, unless the patient is immunocompromised or had severe disease.